Competencies of Newly-Graduated Nurses, Maharaj Nakorn Chiang Mai Hospital - Sapinun, Ladarat; Potacharoen, Orapin; Chokbunyasit, Nidda; Roongruangsri, Supit; Suthachai, Boonrak; Ketson, Khanchai; Phongsanggach, Peeraya; Wichaikhum, Orn-Anong (Biomedical Sciences and Clinical Medicine, 2017)
Background The Nursing Service Division, Maharaj Nakorn Chiang Mai Hospital, has assessed the competencies of newly-graduated nurses annually; however, the assessment has focused on a clinical competency only. All eight nursing competencies issued by the Thailand Nursing and Midwifery Council have not been covered. Objective To explore and compare the competencies of newly-graduated nurses assessed by the newly-graduated nurses and the nurse preceptors. Methods This study was a comparative descriptive research. The samples of this study consisted of 98 newly-graduated nurses working in the Nursing Service Division of Maharaj Nakorn Chiang Mai Hospital in 2014 after graduation for 1 year and 95 nurse preceptors. The researchers developed the Competencies for Newly-graduated Nurse Scales assessed by the newly-graduated nurses and the nurse preceptors based on the competencies of registered nurses issued by the Thailand Nursing and Midwifery Council. The content validity index for both scales were 0.90. The Cronbach alpha of the scales assessed by the newly-graduated nurses and the nurse preceptors were 0.97 and 0.95, respectively. Data were analyzed using average, standard deviation and t-test Results The self-assessed competency of the newly-graduated nurses for ethics and codes of ethics and laws was at a high level ( = 4.29, S.D= 0.60). The competency ofacademics and research was at a low level ( = 3.68, S.D= 0.69). The competency of the newly-graduated nurses assessed by the nurse preceptors was found at a high level for professional characteristics ( = 4.72, S.D= 0.70) and the low level for the academics and research ( = 3.63, S.D. = 0.92). The overall average scores of self-assessed nursing competencies assessed by the newly-graduated nurses and the nurse preceptor were at a high level ( = 170.81, S.D. = 17.90: =172.10, S.D. = 18.66, respectively). Moreover, there was no statistically signi fi cant difference between the competency scores assessed by the newly-graduated nurses and the nurse preceptor (t =0.48, p=0.63). Conclusion The overall average scores of self-assessed nursing competencies assessed by the newly-graduated nurses and the nurse preceptor were at a high level. There was no statistically signi fi cant difference between the competency scores assessed by the newly-graduated nurses and the nurse preceptor The Nursing Service Division should develop the academics and research competencies of newly-graduated nurses. Factors affecting the competencies of newly-graduated nurses should be explored.